2019
DOI: 10.1111/php.13143
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Long‐Wavelength Ultraviolet A1 and Visible Light on Light‐Skinned Individuals

Abstract: Solar radiation is known to be a major contributor to the development of skin cancer. Most sunscreen formulations, including those with broad spectrum, offer minimal protection in long‐wavelength ultraviolet A1 (UVA1; 370–400 nm) and visible light (VL; 400–700 nm) domain. There is limited information regarding the impact of this broad waveband (VL + UVA1, 370–700 nm) on those with light skin. In this study, ten healthy adult subjects with Fitzpatrick skin phototypes I–III were enrolled. On day 0, subjects' low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 9 publications
1
44
0
Order By: Relevance
“…17 Combining LUVA1 and VIS cause an immediate erythema response in skin phototype I-III, while inducing inflammation and immediate pigment darkening in skin phototype IV-VI. [6][7][8] VIS alone or in combination with IR generates ROS, increases collagen degradation, and indirectly leads to DNA damage. 18,19 Since VIS and IR makeup a great proportion of solar radiation and due to the lack of sunscreens offering protection beyond UV, it is crucial that novel means of photoprotection against these longer wavelengths be developed and tested.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 Combining LUVA1 and VIS cause an immediate erythema response in skin phototype I-III, while inducing inflammation and immediate pigment darkening in skin phototype IV-VI. [6][7][8] VIS alone or in combination with IR generates ROS, increases collagen degradation, and indirectly leads to DNA damage. 18,19 Since VIS and IR makeup a great proportion of solar radiation and due to the lack of sunscreens offering protection beyond UV, it is crucial that novel means of photoprotection against these longer wavelengths be developed and tested.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] It has been shown that long wavelength UVA1 (LUVA1) combined with VIS can result in erythema in skin phototype I-III, plus darker, persistent pigmentation and inflammation in subjects with skin phototype IV-VI. [6][7][8] Various protocols consisting of single or multiple exposures have been published to investigate the mechanism of VIS-induced skin darkening. [3][4][5][6][7][8][9] Growing evidence indicates that pigment formed at earlier time points after VIS irradiation is photo-oxidized melanin while, at later time points, new pigments are synthesized through neo-melanogenesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We have not found studies on the role of VL in this dermatosis, although VL has been linked to diverse photoaggravated disorders such as melasma, postinflammatory hyperpigmentation, cutaneous porphyrias, and solar urticaria 14 . Furthermore, VL can trigger immediate erythema in light‐skinned individuals, through a synergistic effect with UVA1 15 …”
Section: Resultsmentioning
confidence: 98%
“…Regarding the impact of nutrition on rosacea, patients report certain foods as triggers such as spicy food (capsaicin), fatty food, those containing cinnamaldehyde (chocolate tomatoes and citrus 15 ), alcohol, and hot beverages 18 as triggers 19 . Capsaicin and cinnamaldehyde can trigger TRP and promote vasodilation and flushing 11 .…”
Section: Resultsmentioning
confidence: 99%